2003
DOI: 10.1109/tbme.2002.807640
|View full text |Cite
|
Sign up to set email alerts
|

Biological constraints simplify the recognition of hand shapes

Abstract: This study sought to identify constraints that might lead to a concise system of recognizing fingerspelling hand shapes. Previous studies of grasping suggested that hand shape is controlled using combinations of a small number of neuromuscular synergies, but fingerspelling shapes appear to be more highly individuated and, therefore, might require a larger number of degrees of freedom. Static hand postures of the American Sign Language manual alphabet were recorded by measuring 17 joint angles. Principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 10 publications
5
32
0
Order By: Relevance
“…The study of the principal components [7], [25], [26] of grasping has provided another method for the control of a myoelectric hand. Santello et al.…”
Section: Mathematical Coupling Using Principal Componentsmentioning
confidence: 99%
“…The study of the principal components [7], [25], [26] of grasping has provided another method for the control of a myoelectric hand. Santello et al.…”
Section: Mathematical Coupling Using Principal Componentsmentioning
confidence: 99%
“…This so-called dissimilation may support visual discrimination of words and recognition by the observer. Consequently, dissimilation was predominant for the index and middle finger joints which are known to be fundamental for letter recognition (Jerde et al, 2003b).…”
Section: Sequencing and Coarticulation In Limb Movementsmentioning
confidence: 99%
“…Based on the principal component analysis, Jerde et al ( Jerde et al (2003)) found support for the existence of postural synergies of angular configuration. The shape of human hand can be predicted using a reduced set of variables and postural synergies.…”
Section: Dimensionality Reduction Methods For Extracting Synergiesmentioning
confidence: 99%
“…(i) Postural synergies: In Jerde et al (2003); Mason et al (2001); Santello et al (1998;; Thakur et al (2008); Todorov & Ghahramani (2004), researchers found that the entire act of grasp can be described by a small number of dominant postures, which were defined as postural synergies.…”
Section: Synergiesmentioning
confidence: 99%